Relevance of Coast Guard Public Affairs Service: Basis for Development of Officer’s Course Instructional Guide - Leanda, Jem Marie D (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
With the rapid change of information environment, this study explored the relevance of the Coast Guard Public Affairs Service (CGPAS) in executing the functions of the Philippine Coast Guard (PCG). The research highlights the essential skills of Public Affairs Officers (PAOs) in these areas: Media Relations, Public Information Dissemination, and Social Media Management in promoting a positive image of the PCG. The study utilized survey and interview to gather data from 40 PAOs, majority with the rank of Ensigns, with at least six months PAO experience; 84 Heads of Offices (HOs), who were mostly Captains; and four Subject Matter Experts (SMEs) in Public Affairs, Education, and Training, all from the PCG. Results revealed that PAOs, HOs and SMEs concurred on the crucial role of CGPAS in the execution of PCG functions, particularly in crisis communication and public image promotion. In terms of skill levels of PAOs, the overall scenario-based exam results coincided with the overall HO’s perception. Both were equivalent to Competent, based on the Dreyfus Model of Skill Acquisition. The study also identified challenges faced by PAOs, including role overload from multiple designations and inadequate resources such as office space, trained spokesperson and PA equipment. Recommendations included providing better equipment, comprehensive trainings on crisis communication, news writing and cybersecurity, fostering organizational collaboration, and recruiting specialists. Finally, a Course Instructional Guide for Public Affairs Officers was developed and proposed for adoption and implementation to hone their effectiveness in promoting the PCG’s mission and functions.